VALUE-ORIENTED FACTORS IN THE MANAGEMENT OF ECONOMIC SECURITY OF ENTERPRISES OF NETWORK STRUCTURES - STETSKO, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article proposes a mechanism for managing the economic security of enterprises of network structures, defines the main functional goals of this security, and outlines the list of external and internal factors that affect it. Strategic development is highlighted as preventive management of economic security of network structures. Modern aspects of the formation of approaches to value-oriented financial management of enterprises of network structures are outlined, and the need to transform management approaches to finance in the context of a new paradigm of financial management is determined.It is proven that the introduction of modern technologies into the management system of enterprises of network structures, within the framework of the global development of the digital economy, requires a rethinking of the financial flow management system in business processes aimed at assessing the value of business in the overall financial management system.The effectiveness of the influence of modern concepts of value-oriented management on the profitability of the enterprises of network structures during their activity is determined. An analysis of the components of the process of value-oriented management, components and principles was carried out, and modern features of adaptation of these elements to the processes of managing financial flows of enterprises of network structures were determined.
Keywords: enterprises of network structures; economic security; system of economic security; management of economic security; strategy of economic security of network structures; mechanism of formation of economic security; value-oriented management; ensuring the growth of enterprise value; potential of enterprises